Evaluating the Environmental Impact of the Industry of Panela by Life Cycle Analysis - Moreno , C. Walter Francisco Quezada; Moya , C. Ana Margarita Contreras; Domínguez , C. Elena Rosa; Torres , David Quezada; Borja , Mg. Franklin Antonio Molina; Molina , Mg. Jaime Orlando Rojas (Current Overview on Science and Technology Research Vol. 9, 2022)
The goal of the study is to evaluate the environmental effects caused bythe industry of the panela in Ecuador using the Life Cycle Analysis approach.. In the agroindustry of panela the activities of handcrafted character prevail over the activities of industrial character. The in-situ data acquired made it possible to identify the delicate environmental elements that have an impact on all of the operations carried out in the panela agroindustry. Due to low industrial development, the application and control of regulations, rudimentary manufacturing practises, among other factors, the results demonstrate that craft activities predominate over industrial activities, which has resulted in insufficient productivity, competitiveness, quality, and safety of their products. According to the Life Cycle Analysis technique, the outcomes of the Environmental Impact Assessment using the Eco-Indicator 99 method demonstrate that the industrial stage has the greatest contribution to the impact, being more representative of the impact to the effects of inorganic compound respiration, acidification / eutrophication, climate change, and land use. According to Ecuador's environmental legislation, the impact level of this type of industry is moderate, requiring no intensive protective or corrective measures. To mitigate these effects, however, environmental executive actions aimed at control and prevention are required.